Gravitational waves in f(R) gravity power law model - Gogoi, Dhruba Jyoti; Dev Goswami, Umananda (Indian journal of physics, 2022)
We investigate the different polarization modes of gravitational waves in f ( R ) gravity power law model in de Sitter space. It is seen that the massive scalar field polarization mode exists in this model. The mass of the scalar field depends highly on the background curvature and the power term n . However, we found that the model does not exhibit a massive scalar mode for n = 2 and instead, it shows a breathing mode in addition to the tensor plus and cross modes. Thus, mass of the scalar field is found to vary with n within the range 1 ≤ n ≤ 2 .